IMPACT OF RADIOACTIVE EXPOSURE ON HUMAN HEALTH AND STRATEGIES FOR RADIATION PROTECTION (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Nowadays, the problems of ensuring the safety of human life have become even more acute. The frequency and destructive power of accidents, fires, incidents and disasters in countries and regions of the world are increasing year by year. Thousands of people die as a result of these emergencies, and unprecedented economic and other types of damage are being caused. Therefore, the issues of protection from various dangers, including radiation safety, are of great importance.